Discourse Analysis: Language Issues in Indigenous Language Learning in Indonesia - Moses Adeleke Adeoye; Entika Fani Prastikawati; Lulut Widyaningrum (Universitas PGRI Semarang, 2024)
This article examines the complexities of language issues in the context of Indigenous language learning in Indonesia, a nation with over 700 living languages. Indigenous languages are at risk of extinction due to socio-political and economic factors. The research examines the role of language policies, educational practices, and community engagement in preserving and revitalizing Indigenous languages. It highlights the challenges Indigenous communities face in accessing quality language learning resources and the impact of globalization on language transmission. The discourse surrounding Indigenous language learning in Indonesia reveals the importance of these languages in cultural identity and heritage. In Indonesia, many Indigenous languages are classified as endangered, and there is an urgent need to address the barriers to effective language learning. The Indonesian government's language policy has historically prioritized the national language, Bahasa Indonesia, often marginalizing Indigenous languages. This policy environment creates significant challenges for Indigenous language learners, who may find themselves without adequate resources or support. Schools in many regions do not offer Indigenous language programs; when they do, the curriculum often lacks cultural relevance. Discourse analysis reveals that Indigenous communities often possess rich linguistic resources and knowledge that can contribute to language teaching. Collaborative efforts between educators, community leaders, and linguists can create a more inclusive language learning environment. Initiatives such as language nests, immersion programs, and local storytelling can enhance the learning experience by making it culturally relevant and engaging. By fostering a discourse that values and promotes linguistic diversity, Indonesia can work towards preserving and revitalizing Indigenous languages.